Realization of highly realistic broadcast that includes the eye movements of basketball players - Kitahama, K.; Sarugaku, T.; Yamada, M. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
Sport spectatorship changes with the introduction of new technologies. There are many video editing methods in sports broadcasting, but it is more important to base video presentation on the characteristics of a specific sport. We examined the eye movements of basketball players and found. An essential relationship between their skill level and their eye movements in making successful shots. Analysis of eye movements during free throws revealed that a player was more likely to score if they focused on the support frame line on the backboard not only before the shot but even after releasing the ball. Overlaying reveals the movements of both players and their focus simultaneous analysis. Overlaying technology proved that spectators could watch a player`s focus and body movement specifically at the same time. By recording with 4K video cameras, spectators could easily understand the directions of the players. Furthermore, we proved that the analysis of a player's eye movement in a play s ituation can be beneficial to the team. As a result of this study, the differences in court awareness during a play according to the skill levels of different players became apparent.